Development of Environment-Based Pop Up Book Media to Help Beginning Reading Skills for Children Aged 5-6 Years in Kindergarten ABA 05 Medan - Ade Irma Suryani Siregar; Aman Simaremare (Indonesian Journal of Advanced Research, 2023)
This research aims to; 1) Find out how the results of the validation of the Environment-Based Pop Up Book media were developed to help beginning reading skills in children aged 5-6 in Kindergarten ABA 05 Medan. 2) To find out whether the practicality of the Pop Up Book media developed is appropriate to be used to assist beginning reading skills in children aged 5-6 years at ABA 05 Kindergarten Medan. The research method used is Research and Development (R&D), using the ADDIE model development, referring to (Analysis, Design, Development, Implementation, Evaluation). The subjects in the study were group B students at TK ABA 05 Medan, to be precise, class B3 with 9 boys and 4 girls, while the research object was Pop Up Book media using assessment instruments from the validation of material experts and media experts, as well as the practicality of classroom teacher. The results of the material expert validator and media expert obtained the percentage of all aspects of the media by 95% with the very valid category, while the total percentage of media practicality test scores was 83% with the very practical category. The results of this study were successful in developing a product in the form of an Environment-Based Pop Up Book learning media aimed at helping the beginning reading skills of children aged 5-6 years in Kindergarten ABA 05 Medan. The conclusion of this study is that the developed Environment-Based Pop Up Book media is in a valid and practical category.